TERP: a trust and energy aware routing protocol for wireless sensor network - Ahmed, Adnan (Institute of Electrical and Electronics Engineers Inc., 2015)
In most of the applications of wireless sensor networks (WSNs), nodes operate in unattended environments and are, therefore, vulnerable to variety of attacks. Due to dynamic and unpredictable changing behavior of nodes, the reliable data delivery is a challenging task. For WSNs, the traditional cryptographic and authentication-based solutions cannot be adopted due to their associated cost and incapability to counter nodes misbehavior attacks. Recently, trust-based solutions have proved to be more effective to address nodes' misbehavior attacks. However, the existing solutions give rise to high energy consumption and control overheads in pursuit of trust estimation and network-wide dissemination, which not only adds to network congestion but also undermines network lifetime. In this paper, we present a trust and energy aware routing protocol (TERP) that makes use of a distributed trust model for the detection and isolation of misbehaving and faulty nodes. Moreover, TERP incorporates a composite routing function that encompasses trust, residual-energy, and hopcounts of neighbor nodes in making routing decisions. This multi-facet routing strategy helps to balance out energy consumption among trusted nodes, while routing data using shorter paths. The simulation results demonstrate reduced energy consumption, improved throughout and network lifetime of TERP when compared with the existing work.